A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Randomized trial in rural Native American homes heated with wood stoves: results from the EldersAIR study - Curtis W. Noonan; Ethan S. Walker; Erin O. Semmens; Annie Belcourt; Johna Boulafentis; Crissy Garcia; Jon Graham; Nolan Hoskie; Eugenia Quintana; Julie Simpson; Paul Smith; Howard L. Teasley; et al. (Air Quality, Atmosphere & Health, 2024)

Disruption of Sonic Hedgehog Signaling Accelerates Age-Related Neurogenesis Decline and Abolishes Stroke-Induced Neurogenesis and Leads to Increased Anxiety Behavior in Stroke Mice - Jiapeng Wang; Kierra Ware; Alicia Bedolla; Emily Allgire; Flavia Correa Turcato; Maxwell Weed; Renu Sah; Yu Luo (Translational Stroke Research, 2022)

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

Challenges and opportunities for neuroimaging in young patients with traumatic brain injury: a coordinated effort towards advancing discovery from the ENIGMA pediatric moderate/severe TBI group - Emily L Dennis; Karen Caeyenberghs; Robert F Asarnow; Talin Babikian; Brenda Bartnik-Olson; Erin D Bigler; Anthony Figaji; Christopher C Giza; Naomi J Goodrich-Hunsaker; Cooper B Hodges; Kristen R Hoskinson; Marsh Königs; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Postnatal exposure to MK801 induces selective changes in GAD67 or parvalbumin - Christopher Paul Turner; Danielle DeBenedetto; Emily Ware; Robert Stowe; Andrew Lee; John Swanson; Caroline Walburg; Alexandra Lambert; Melissa Lyle; Priyanka Desai; Chun Liu (Experimental Brain Research, 2010)

An Automated Approach to Salt Selection for New Unique Trazodone Salts - Emily C. Ware; D. Robert Lu (Pharmaceutical Research, 2004)